Pengembangan Handout Berbasis Hasil Penelitian Daya Antagonisme Kapang Antagonis dan Kapang Patogen pada Tanaman Tomat - Dina Istia’nah; Utami Sri Hastuti; Abdul Gofur (Bioscientist : Jurnal Ilmiah Biologi, 2020)
This study aims to produce valid and practical handouts for use in the learning process. This research was conducted in March-May 2020. The development model used is the ADDIE model, which consists of Analyze, Design, Develop, Implement, and Evaluate stages. Handout material is based on the results of research that has been carried out. The subject of the handout trial included a validator of Microbiology material experts, an expert validator of learning media, and a legibility test by 30 students of the Undergraduate Biology Education Study Program, FMIPA, State University of Malang who had taken the Microbiology course to assess the practicality of the handouts. Data collection techniques through distributing questionnaires and interviews. The data collection instruments were in the form of a validation sheet and a legibility test sheet containing handout assessment indicators. The results showed that, the Microbiology handout had a validation score of 98.25% from experts in Microbiology, and a validation score of 99.5% from instructional media experts with very valid criteria. While the readability test results by students obtained a score of 87.18% with very practical criteria. Based on the results of this assessment, it can be concluded that the handout "Antagonistic Power between Antagonistic Fungi and Pathogenic Fungi in Tomato Plants (Lycopersicum esculentum Mill.)" Is declared valid and practical to be used as microbiology teaching materials.